Glucocorticoid-Induced Osteoporosis: The Potential Role of Romosozumab - Jacqueline So; Chi Chiu Mok (Journal of Clinical Rheumatology and Immunology, 2020)
Glucocorticoid (GC)-induced osteoporosis (GIOP) is a major problem in patients with rheumatic diseases. The deleterious effect of GC on bone turnover is rapid and dose-dependent, with a predilection on the trabecular bone, resulting in vertebral fractures. Early recognition and prompt treatment of GIOP helps prevent bone loss and reduce fractures. There are pitfalls in current assessment tools for GIOP by dual-energy X-ray absorptiometry (DXA) and fracture risk assessment tool (FRAX) estimation formula. In this review, we evaluate different assessment methods for GIOP and summarize current therapies of GIOP, including the antiresorptive and anabolic agents. The potential role of newer anti-osteoporosis agent romosozumab, an anti-sclerostin monoclonal antibody, is also discussed.